The Corrosion Behavior of Sputter-deposited W-Ti Alloys in 0.5 M NaCl Solution - Bhattarai, Jagadeesh (Nepal Journal of Science and Technology, 2010)
The corrosion behavior of the sputter-deposited amorphous or nanocrystalline W-Ti alloys was studied in neutral 0.5 MNaCl solution at 25°C, open to air by immersion tests, electrochemical measurements and confocal scanning laser microscopic(CSLM) techniques. Titanium metal acts synergistically with tungsten in enhancing the corrosion resistance of the sputter-deposited W-Ti alloys so as to show higher corrosion resistance than those of alloy-constituting elements (that is, tungsten and titanium) in neutral 0.5 M NaCl solution. In particular, the amorphous W-Ti alloys containing 30-53 at% titanium showed lowest corrosion rates (that is, about 1 × 10-3 mm.y-1). Open circuit potentials of all the examined W-Ti alloys were shifted to more noble direction than those of the open circuit potentials of alloyconstituting elements in 0.5 M NaCl solution. Key words: Sputter deposition; W-Ti alloys; Corrosion-resistant; CSLM; NaCl solution. DOI: 10.3126/njst.v10i0.2899 Nepal Journal of Science and Technology Volume 10, 2009 December Page:109-113